A problemática do saneamento nas comunidades litoraneas da reserva de desenvolvimento sustentavel estadual ponta do tubarão e os impactos na qualidade da água estuarina - Ferreira Filho, Joilson Marques (Universidade Federal Rural do Semi-Árido, 2017)
Balneability is the quality of the water destined to the recreation of primary contact, for a significant time with water, where it is possible to ingest significant amounts of it. Thus, the general objective is to verify the quality of the estuarine waters of the Ponta do Tubarão State Sustainable Development Reserve (RDSEPT) through environmental and social indicators. For this, the research was carried out in the estuary that bathes the communities of Chico Martins, Barreiras, Diogo Lopes and Sertãozinho, belonging to RDSEPT. The data were measured in the estuarine border of the communities of Chico Martins, Barreiras, Diogo Lopes and Sertãozinho in five distinct geo-referenced points and also the negative environmental impact survey through checklist and photographic registers. For the measurement of the environmental indicators, water samples were collected for microbiological and physico-chemical analyzes and observation of negative environmental impacts through checklist and photographic registers. As for socio-environmental data, data collection was carried out between August and December 2016, through a field survey and a structured interview with the help of a semi-structured questionnaire with multiple answers, answered by 384 residents. The physico-chemical data were collected through multi-parameter equipment and the microbiological research was performed through cytological, macroscopic and biochemical tests to identify microorganisms. According to the standard for saline water and the results for total coliforms and thermotolerant water, values within the limits established in the legislation were found in 90% of the samples, and 100% of the Escherichia coli and Enterococcus sp samples, being considered Excellent category. On the other hand, the checklist was georeferenced 205 points of domestic effluent discharge and 7 areas of inadequate disposal of urban solid waste in an estuary area, which classifies estuary water as inappropriate for bathing. Concerning the sociodemographic data, it was observed that the majority of the residents are male, with low level of schooling and that the vast majority have been fishing and have lived for more than 20 years in their community. Still according to the results, most of the interviewees use the estuary water for fishing or leisure, considers the water quality good, however, it affirms the presence of domestic effluents, the inadequate disposal of urban solid waste and the presence of domestic animals in an estuary area. It is concluded that the estuarine waters of the Ponta do Tubarão State Sustainable Development Reserve present the physico-chemical indices according to established standards and are contaminated with faecal bacteria, with concentrations below the permitted limits, however, all along its path, the shoreline presents the inadequate disposal of municipal solid waste, the launching of domestic and / or sanitary effluents, considering the section searched inappropriate by Resolution No. 274/2000 of CONAMA. Regarding the environmental perception, despite the high number of sewage and waste streams in the estuary and the presence of animals on the waterfront, residents say that estuarine water is adequate for consumption
The problem of sanitation in the coastal communities of the ponta do tubarão state sustainable development reserve and the impacts on the quality of the estuarine water
Keywords: Balneabilidade; Unidades de Conservação; Bioma Caatinga; Percepção Ambiental; RDSEPT; Balneability; Conservation units; Caatinga Biome; Environmental Perception; RDSEPT; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE